Doctrinal and advocacy contents in his farewell sermon (Journal of the College of Basic Education, 2022)
To proceed, the honorable biography of the Prophet, upon its owner, the best prayers and peace at the level of roses and deduction is a source of legislation, belief, morals, and the call to God Almighty, and it is of great importance that research studies deal with it reading, deduction, and the formation of doctrinal, advocacy, legislative, and moral outputs that contribute to building the individual and society, and prepare The farewell sermon is an important resource for taking these outputs, and this study preceded what the compilers wrote in the biography of the Prophet, may God’s prayers and peace be upon its author, from previous and updated studies that enriched researchers in this science and those familiar with it